Electro-nuclear quantum phase transition in TmVO 4 - Mark P. Zic; Chao Huan; Nicolas Silva; Yuntian Li; Mark W. Meisel; Ian R. Fisher (Proceedings of the National Academy of Sciences, 2026)
Hyperfine interactions couple nuclear and electronic degrees of freedom. The present work explores how hyperfine coupling within the Tm ions in TmVO 4 single crystals affects an electronic ferroquadrupole ordered ground state and its associated field-tuned quantum phase transition. As temperature is progressively reduced through the hyperfine energy scale, the nuclear moments reduce the critical field for the electronic order, resulting in a dramatic back-bending of the phase boundary delineating the ferroquadrupole order. This behavior is well described by a single-ion semiclassical mean-field model down to approximately 50 mK. Analysis of the effective Hamiltonian leads to a prediction of spontaneous nuclear magnetic order mediated by 4 f electrons, which in principle persists with the application of orthogonal antisymmetric strain, yielding a proposed electro-nuclear tetracritical point.